2010
DOI: 10.1103/physrevb.81.224102
|View full text |Cite
|
Sign up to set email alerts
|

Phase diagram ofTi50xNi50+x: Crossover from martensite to strain glass

Abstract: We systematically investigated the variation in transition behavior and physical properties over a wide excess Ni ͑acting as defect͒ concentration range ͑x =0-2.5͒ in Ti 50−x Ni 50+x alloys. This enables the establishment of an updated quantitative phase diagram for this important system. The phase diagram shows not only the well-known parent phase and martensite phase but also a premartensitic state and a strain glass state. Our experiments were able to determine quantitatively the borders of these states, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
101
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 90 publications
(112 citation statements)
references
References 36 publications
11
101
0
Order By: Relevance
“…Point defects have been known to play a central role in altering and controlling the properties of ferroelastic materials [1]. In addition to the well-known paraelastic and ferroelastic strain states, it was found that point defects can generate two abnormal strain states: a ''precursory strain state'' (or tweed) characterized by a cross-hatched nanosized strain domain structure [2,3] imbedded in a dynamically disordered paraelastic matrix [4] and a new strain-glass state that is a frozen state of local strain order [5][6][7][8], a ferroelastic analogue to ferroelectric relaxors [9] and cluster spin glasses [10,11].Recent experimental studies have yielded strikingly similar ''phase diagrams'' of strain states for many different doped ferroelastic systems [12][13][14]. An example is given in Fig.…”
mentioning
confidence: 99%
“…Point defects have been known to play a central role in altering and controlling the properties of ferroelastic materials [1]. In addition to the well-known paraelastic and ferroelastic strain states, it was found that point defects can generate two abnormal strain states: a ''precursory strain state'' (or tweed) characterized by a cross-hatched nanosized strain domain structure [2,3] imbedded in a dynamically disordered paraelastic matrix [4] and a new strain-glass state that is a frozen state of local strain order [5][6][7][8], a ferroelastic analogue to ferroelectric relaxors [9] and cluster spin glasses [10,11].Recent experimental studies have yielded strikingly similar ''phase diagrams'' of strain states for many different doped ferroelastic systems [12][13][14]. An example is given in Fig.…”
mentioning
confidence: 99%
“…All the determined characteristic temperatures, T 0 , T Ms , and T Af , are listed in Table 1 and plotted in Fig. 2 as a function of x together with data from some previous reports [1,7,[10][11][12][13][14][15][16][17], T 0 being approximated as the average of T Ms and T Af in this study. T Ms in 49.98 Ni (338 K) well accords with that in the slowly cooled stoichiometric TiNi (333 K) [16].…”
Section: Determination Of Transformation Temperaturesmentioning
confidence: 98%
“…Meanwhile, from the scientific viewpoint, Ti-Ni and its derived SMA systems continue to engender fundamental interest in the nature of B2/B19 0 martensitic transformation (MT). In the Ni-rich portion of the Ti-Ni system, it is well known that the MT start temperature (T Ms ) suddenly disappears at around 51.4 at.% Ni [1]. Such a suppression of MT has only been explained so far by the concept of strain glass, which is one of the class of glassy states in transformation strain essentially similar to spin glass and relaxor [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…As anticipated in a preceding subsection these authors attributed the modulus dip and the IF peak to a local strain glass transition, which was subsequently further investigated by X-rays, electron microscopy, zero-field cooling/field cooling and static stress-strain experiments (Refs. [24][25][26][27][28][29][30][31]35). Their X-ray diffraction patterns are shown in figure 18(a) while the IF and the Young's modulus results (Refs.…”
Section: Alloys Contaminated With Hydrogenmentioning
confidence: 99%
“…7,9,14,15,17,19,23,30,[45][46][47][48][49][50][51][52][53]. Remaining questions to be answered are: a) the origin of the non-thermally activated peaks P 150K and P 200K and b) the role of H in the local strain glass transition.…”
Section: H-contaminated Materialsmentioning
confidence: 99%